Implementasi model problem-based learning seting student team achievement division dalam meningkatkan kemampuan pemecahan masalah dan minat belajar matematika - Siti Rahmalia Natsir; Samritin Samritin (EKSPOSE, 2020)
The purpose of this study is to describe the results of the application and application of the Problem-Based Learning learning model in the STAD type cooperative settings in improving problem-solving abilities and students' interest in learning mathematics. This research is a type of CAR. The subjects in this class action research of Va SD Negeri 2 Baubau elementary school. Data were collected using tests of problem-solving abilities, questionnaire interest in learning mathematics and observation. Evaluation of first cycle obtained an average grade of 60.71 with the percentage of students' learning ability 40.63% and interest in learning mathematics in the very high category had a percentage of 6.25%, the high category had a percentage of 25% and the medium category had a percentage 38% and low category had a percentage of 31%. In first cycle , the learning performance was 92%. In second cycle, the average class is 85.71 with the percentage of students' learning ability 90.63% and the interest in learning mathematics in the very high category has a percentage of 28.39%, the high category has a percentage of 59% and the medium category as a percentage of 13% and 0 % of the interest in categories is low and very low. Implementation of learning by 97%. Based on the results of research and discussion, it can be concluded that the application of the PBL setting STAD can improve the problem solving skill and students' interest in learning mathematics.Penelitian ini bertujuan untuk mendaskripsikan hasil penerapan Problem-Based Learning (PBL dalam seting kooperatif tipe Student Team Achievement Division (STAD) dalam meningkatkan kemampuan pemecahan masalah dan minat belajar matematika. Penelitian ini termasuk jenis Penelitian Tindakan Kelas (PTK). Subjek dalam penelitian tindakan kelas ini adalah kelas Va SD Negeri 2 Baubau sebanyak 32 murid. Data dikumpulkan menggunakan tes kemampuan pemecahan masalah, angket minat belajar matematika dan lembar observasi. Evaluasi siklus pertama diperoleh nilai rata-rata kelas sebesar 60,71 dengan persentase kentutasan belajar murid-murid adalah 40,63% dan minat belajar matematika pada katagori ST memiliki persentase 6,25%, katagori T memiliki persentase 25%, katagori S memiliki persentase 38% dan kategori R memiliki persentase 31%. Pada siklus pertama keterlaksanaan pembelajaran 92%. Siklus kedua rata-rata kelas 85,71 dengan persentase kentutasan belajar murid-murid adalah 90,63% dan minat belajar matematika pada katagori ST memiliki persentase 28,39%, katagori T memiliki persentase 59% dan katagori S memiliki persentase 13% dan 0% minat dalam ketegori R dan sangat SR. Keterlaksanaan pembelajaran sebesar 97%. Berdasarkan hasil penelitian dan pembahasan, maka dapat disimpulkan bahwa penerapan model PBL dalam seting STAD dapat meningkatkan kemampuan pemecahan masalah dan minat belajar matematika murid-murid.